Modulation of flagellum attachment zone protein FLAM3 and regulation of the cell shape in Trypanosoma brucei life cycle transitions - Sunter, Jack D; Benz, Corinna; Andre, Jane; Whipple, Sarah; McKean, Paul G; Gull, Keith; Ginger, Michael L; Lukeš, Julius (Journal of cell science, 2015)
The cell shape of Trypanosoma brucei is influenced by flagellum-to-cell-body attachment through a specialised structure - the flagellum attachment zone (FAZ). T. brucei exhibits numerous morphological forms during its life cycle and, at each stage, the FAZ length varies. We have analysed FLAM3, a large protein that localises to the FAZ region within the old and new flagellum. Ablation of FLAM3 expression causes a reduction in FAZ length; however, this has remarkably different consequences in the tsetse procyclic form versus the mammalian bloodstream form. In procyclic form cells FLAM3 RNAi results in the transition to an epimastigote-like shape, whereas in bloodstream form cells a severe cytokinesis defect associated with flagellum detachment is observed. Moreover, we demonstrate that the amount of FLAM3 and its localisation is dependent on ClpGM6 expression and vice versa. This evidence demonstrates that FAZ is a key regulator of trypanosome shape, with experimental perturbations being life cycle form dependent. An evolutionary cell biology explanation suggests that these differences are a reflection of the division process, the cytoskeleton and intrinsic structural plasticity of particular life cycle forms.
Keywords: tvar buňky; vývojová regulace genové exprese; Morphogenesis; Gene Expression Regulation, Developmental; stadia vývoje; Flagella; Flagellum attachment zone; Cytoskeleton; protozoální proteiny; flagella; Trypanosoma brucei brucei; Microtubules; cilie; Trypanosomes; Animals; zvířata; mikrotubuly; cytokineze; cytoskelet; Life Cycle Stages; Cilia; Protozoan Proteins; Cell Shape; Cytokinesis